Pengembangan Bahan Ajar Numerasi Berbasis Wisata Jawa Barat untuk Penalaran Kritis Siswa SD - Eka Firmansyah; Achmad Mudrikah; Siti Nurhayati; Feri Husada Susanto; Melinda Putri Mubarika; Jasem Al- Tamar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
This study aimed to develop and evaluate West Java tourism-based numeracy teaching materials designed to foster critical thinking among elementary school students. The study employed a Research and Development approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. Needs analysis involved curriculum review, interviews, and questionnaires administered in three elementary schools. The product was developed for fourth- and fifth-grade students and consisted of a numeracy module, student worksheets, and a teacher guide integrating measurement, estimation, arithmetic operations, and simple data analysis with authentic contexts from Kawah Putih, Tangkuban Perahu, and Pangandaran Beach. Product validity was assessed by three experts in mathematics education, curriculum, and elementary education, while practicality was examined through teacher and student response questionnaires. A limited field trial involving 75 students used pre-test and post-test tasks to assess numeracy and critical thinking, supported by classroom observations. The expert validation yielded an overall mean score of 3.55 on a four-point scale, indicating that the materials were very valid. Teacher and student responses ranged from 85% to 90%, placing the materials in the very practical category. Post-test performance increased by 25% compared with pre-test performance, indicating meaningful gains in students’ numeracy achievement after using the materials. Students also demonstrated stronger abilities to identify relevant information, analyze quantitative relationships, evaluate solution strategies, and draw logical conclusions in contextual tourism problems. These findings indicate that the developed materials are valid, practical, and potentially effective for meaningful numeracy learning. Broader trials are recommended to examine their effectiveness across diverse elementary school contexts.